Determinantes da satisfação no trabalho dos servidores técnico-administrativos da Universidade Federal de Santa Maria: avaliação via duas escalas de medidas - Smidt, Maristela Ribas (2020)
Public institutions have undergone transformations that directly affect their structure and functioning. A prominent factor in this new organizational dynamic is job satisfaction. In this sense, the main objecti ve of this study was to describe the level of job satisfaction of the technical administrative staff of UFSM. In methodological terms, this is a descriptive study with a quantitative approach, and a survey was used as the research strategy. To collect the data, we used a poll with questions regarding the professional and socioeconomic profile, the Siqueira Job Satisfaction Scale (2008), which evaluated job satisfaction based on five aspects (colleagues, manager, promotions, salary, and work) and the S20/23 Job Satisfaction Questionnaire by Carlotto and Câmara (2008), which measures intrinsic relationships, the physical environment and hierarchical relationships in relation to work. Statistical factor analysis and regression analysis techniques were used. The results of the survey revealed, in general, that the technical administrative staff are essentially satisfied with the bonds of affectivity between colleagues and managers. However, regarding the organizational context, a feeling of indifference was point ed out, highlighting the need for discussion and redefinition of work routines in order to achieve greater job satisfaction and improve the organization's performance. Therefore, these results can be used as support for managers, especially by the Pro Rect ory of People Management, for the adoption of measures that seek to improve the satisfaction of their employees.